Bexarotene Reduces Production of CCL22 From Tumor-Associated Macrophages in Cutaneous T-Cell Lymphoma - Tanita, Kayo; Fujimura, Taku; Sato, Yota; Lyu, Chunbing; Kambayashi, Yumi; Ogata, Dai; Fukushima, Satoshi; Miyashita, Azusa; Nakajima, Hideki; Nakamura, Motoki; Morita, Akimichi; Aiba, Setsuya (Frontiers in Oncology, 2019)
Bexarotene is a third-generation retinoid X receptor-selective retinoid that is permitted for use in the treatment of both early and advanced cutaneous T cell lymphoma (CTCL). Although bexarotene has been used for decades in the treatment of CTCL, little is known about the mechanisms underlying its anti-tumor effects in CTCL patients. This study therefore focused on the immunomodulatory effects of bexarotene in vivo using an EL4 mouse T-cell lymphoma model, followed by investigation in CTCL patients treated with bexarotene. Intraperitoneal injection of bexarotene significantly decreased expression of CCL22, CXCL5, CXCL10 and p19 in the tumor microenvironment. Based on those results, we then evaluated serum levels of CCL22, CXCL5 and CXCL10 in 25 patients with CTCL, revealing that CCL22 was significantly increased in advanced CTCL compared with early CTCL. Next, we evaluated serum levels of CCL22, CXCL5 and CXCL10 in CTCL patients treated with bexarotene. Serum levels of CCL22 were significantly decreased in 80% of CTCL patients who responded to bexarotene therapy. In addition, immunofluorescence staining revealed that the main source of CCL22 was CD163+ M2 macrophages. Moreover, bexarotene decreased the production of CCL22 by M2 macrophages generated from monocytes in vitro. Our findings suggest that the clinical benefits of bexarotene are partially attributable to suppressive effects on the production of CCL22 by M2-polarized tumor-associated macrophages.